2019
DOI: 10.33132/01248146.997
|View full text |Cite
|
Sign up to set email alerts
|

Factores asociados al retiro temprano del jadelle en un programa de planificación familiar

Abstract: Introducción: Investigación que permitió determinar los factores asociados al retiro temprano de Jadelle® en las usuarias que asisten al programa de planificación familiar en la ESE Santiago de Tunja. Estudio importante para conocer los motivos y las causas de retiro que los profesionales de la salud deben informar a las usuarias para lograr una mayor comprension y aceptación de las reacciones adversas, evitando el retiro temprano del implante.Métodos: Estudio descriptivo, cuantitativo, de corte transversal. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…An independent factor in the adjusted analyses was having presented an adverse event. Regarding adverse effects as a cause for abandonment of HCM, similar results were found in other research [11][12][13] . These authors indicated that the most common adverse effects were headaches, weight gain, and, in the case of implants, uterine hemorrhage.…”
Section: Discussionsupporting
confidence: 89%
“…An independent factor in the adjusted analyses was having presented an adverse event. Regarding adverse effects as a cause for abandonment of HCM, similar results were found in other research [11][12][13] . These authors indicated that the most common adverse effects were headaches, weight gain, and, in the case of implants, uterine hemorrhage.…”
Section: Discussionsupporting
confidence: 89%